KRISIS EKONOMI INDONESIA - Karmeli, Elli (Journal of Indonesian Applied Economics, 2008)
The impact of economic crisis in Indonesia is the occurrence of so many fundamentalchanges  in  the  economic  order,  social,  political,  and cultural  life  of  the  countrywhich determines  the country’s direction.  In one side,  it  is  the biggest changes  inmodern Indonesian history, but on the other hand, it contributes to the complexity ofthe recovery problem economy. The weakness of  the  Indonesian economy, the bigamount  of  the  firm’s  short-term  loans  in  foreign  currency  (dollar) without  anyprotection / hedging, weak banking systems in Indonesia and the weak of the realsectors, could be a lessons for us so that Indonesia will no longer mired in economiccrisis. Besides economic, there are also weakness of political and social structure,financial and banking system, the system of ownership, and also  the system of lawand democratic system itself. Several behaviors that could promote or complicatethe crisis in facing the turmoil of the endurance life is the greater of expendituresthan revenues in both economic activity and living  in a society and state, and  thecrisis of cultural values (the closure, feudalism, and tribalism).Keywords: economic crisis, monetary, rehabilitation